Germination changes of varieties of Vigna mungo L. under tannery effluent stress - T. Ravi Mycin, P. Indra (Recent Research in Science and Technology, 2009)
Wastewater from leather processing, a major industry that produces upto enormous wastewater. The wastewater contains valuable nutrients, but also contaminants, such as salts and chromium (Cr), that might affect soil processes and crop production. The present investigated the different concentrations of tannery effluent on seed germination and seedling growth of ten variety of blackgram (Vigna mungo L.). The results low concentration 10% of tannery waste water promoted the germination, percentage growth, fresh, dry weight of blackgram seedlings, whereas the higher concentration (above 20%) reduced the above all the parameters. The observation also indicates organ specific differences in the growth of seedlings in presence of different concentrations (10, 20, 30, 40, 50 and 100%) of tannery effluent.